Anticlastogenic, radiation antagonistic, and anti-inflammatory activities of Persea americana in albino Wistar rat model - Amith Kumar; Reshma Kumarchandra; Rajalakshmi Rai; Ganesh Sanjeev (Wolters Kluwer Medknow Publications, 2017)
The present study was undertaken to evaluate the anti-inflammatory activity and antigenotoxic effect of hydroalcoholic leaf extract of Persea americana (P. americana) in albino Wistar rats against whole body X-ray irradiation. Rats were orally administered with (25, 50, 100, 200, and 400 mg/kg body weight) of P. americana leaf extract for five days. On the fifth day after last administration, animals were exposed to whole body X-rays of 8 Gy. Based on Kaplan Meier's survival analysis, 100 mg/kg body weight was selected as an optimum dose for radioprotection. The radioprotective potential was analysed by bone marrow micronucleus test and comet assay in peripheral blood lymphocytes. Biochemical estimations were performed in liver tissue homogenates. DNA damage indicators analysed through comet assay displayed significant reduction in olive tail movement (P < 0.01), percentage DNA in tail (P < 0.05) and tail length (P < 0.001) in pretreated group when compared to radiation group. P. americana leaf extract restored the levels of reduced glutathione, catalase, and reduced the levels of lipid peroxidation, protein carbonyls, and cyclooxygenase-2 levels in liver homogenates of pre-treated group. Decrease in micronucleated polychromatic erythrocytes (P < 0.05) was witnessed in P. americana pretreated group when compared to radiation control. Pretreatment also resulted in the increase of animal survival with dose reduction factor of 1.28. Our findings for the first time demonstrated that P. americana offers significant protection to rats from whole body exposure to X-rays and helps in antagonising the radiation effects, thereby combating acute radiation induced damage in living systems.